Is it the injection device or the anxiety experienced that causes pain during dental local anaesthesia? - (:unkn) unknown (WILEY, 2008)
Aim. The aim of this study was to investigate the influence of anxiety and type of dental injection, a plastic syringe or an electronic computerized device, on the pain perceived by children. Design. Two dental injectors, a computerized device (Wand(R), Milestone Scientific, Livingston, NJ, USA) and a traditional plastic syringe, were compared. Forty-one children, aged 9-13 years, who had registered for treatment in Marmara University, Istanbul, Turkey, were included in the study. Both anxious and non-anxious children were included in the study group. The Children's Fear Survey Schedule-Dental Subscale, Facial Image Scale, Spielberger's State Anxiety Index for Children, and heart rates were used to determine the anxiety levels. Participants were assigned to interventions by using random allocation. The first appointment was designed as an introductive familiarization session and injections were administered in the second and third sessions, with one or the other injector. The visual analogue scale was used for pain measurement after injections. Results. No significant differences in injection pain scores were observed between the Wand and traditional plastic injector. Higher levels of pre-injection anxiety were found to be related to more severe pain reports by the children. Conclusions. Anxiety plays an important role in the pain reaction of children, and was found to be more determinative in pain perception than the injection devices preferred.
Keywords: NERVE BLOCK; CHILDREN; WAND